Studies of Sea Surface Temperature and Chlorophyll-a Variations in East Coast of Peninsular Malaysia - Tan, C. K.; Mansor, Shattri; Ibrahim, H. M.; Rashidi, Abdul (Universiti Putra Malaysia Press, 2002)
This paper attempts to classify the oceanographic conditions of the fishing grids in east coast of Peninsular Malaysia using surface chlorophyll-a content and sea surface temperature (SST) data from satellite. The variation of SST and chlorophyll-a content in the South China Sea is greatly affected by the monsoon system. Analysis results showed that both SST and chlorophyll-a variations of the fishing grids are closely related to their geographical locations. The classification using chlorophyll-a on the fishing grids give a clearer variation compared to SST. Hierarchical cluster analysis gave a better means of understanding the variations of these oceanographic conditions and the relationship among the fishing grids. However, to understand how these variations of oceanographic condition affect the marine fisheries catch in Malaysian Exclusive Economic Zone (EEZ), further studies should be conducted using longer time scale data.